Growing up as an individual: - Musarrat Shameem (Crossings, 2009)
This article analyses the character of Ashima Ganguli of the novel The Namesake in two different ways. First it shows how she. as a woman, designs her life combining her traditional beliefs and individual improvisations needed for surviving in a foreign land. Second it also shows how she, as a diaspora mother, adjusts herself to the new way of life in America without effacing her former self completely. The analysis leads to the conclusion that Ashima changes herself in more than one way to mature as an individual with a new personality.